2020
DOI: 10.1038/s41467-020-19637-5
|View full text |Cite
|
Sign up to set email alerts
|

PCM1 is necessary for focal ciliary integrity and is a candidate for severe schizophrenia

Abstract: The neuronal primary cilium and centriolar satellites have functions in neurogenesis, but little is known about their roles in the postnatal brain. We show that ablation of pericentriolar material 1 in the mouse leads to progressive ciliary, anatomical, psychomotor, and cognitive abnormalities. RNAseq reveals changes in amine- and G-protein coupled receptor pathways. The physiological relevance of this phenotype is supported by decreased available dopamine D2 receptor (D2R) levels and the failure of antipsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Some proteins of the ciliome assemble together with a set of scaffold proteins into 70-100 nm cytoplasmic granules known as centriolar satellites [14,15]. Centriolar satellites traffic around centrioles in a microtubule-dependent manner and were found to be important for ciliogenesis in some cell line models [16,17], but a PCM1 knockout mouse only displayed defects in long-term cilia maintenance in some brain tissues [18]. Loss of the centriolar satellite scaffold protein PCM1 interferes with the ciliary localization of several proteins.…”
Section: Involvement Of the Ciliomementioning
confidence: 99%
“…Some proteins of the ciliome assemble together with a set of scaffold proteins into 70-100 nm cytoplasmic granules known as centriolar satellites [14,15]. Centriolar satellites traffic around centrioles in a microtubule-dependent manner and were found to be important for ciliogenesis in some cell line models [16,17], but a PCM1 knockout mouse only displayed defects in long-term cilia maintenance in some brain tissues [18]. Loss of the centriolar satellite scaffold protein PCM1 interferes with the ciliary localization of several proteins.…”
Section: Involvement Of the Ciliomementioning
confidence: 99%
“…Recently, a mouse Pcm1 gene trap was described ( Monroe et al, 2020 ). Aged mice homozygous for this allele exhibited enlarged brain ventricles, progressive neuronal cilia maintenance defects and late-onset behavioral changes, but without perinatal lethality and other early cilia-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Centriolar satellites are dynamic, change in response to cell stresses, and have been implicated in diverse processes including Hedgehog signaling, autophagy, proteasome activity and aggresome formation ( Holdgaard et al, 2019; Hori and Toda, 2017; Joachim et al, 2017; Kubo and Tsukita, 2003; Lecland and Merdes, 2018; Odabasi et al, 2019; Prosser and Pelletier, 2020; Prosser et al, 2020; Tang et al, 2013; Villumsen et al, 2013; Wang et al, 2013a ). Recent work suggested that PCM1 is critical for maintaining neuronal cilia, disruption of which may cause schizophrenic-like features in aged mice ( Monroe et al, 2020 ). Thus, understanding of the function of PCM1 and centriolar satellites is evolving.…”
Section: Introductionmentioning
confidence: 99%
“…2e), regulated the proliferation of neural progenitor cells in mice [51,52]. In humans, PMC1 was found to increase the availability of the dopamine receptor D2 (DRD2) in the brain and associations between PCM1 genetic variants and schizophrenia have been described [53]. The intravenous administration of a synthetic corticotropin-releasing hormone in humans increased both the cortisol stress hormone in blood and dopamine in the dorsal striatum according to positron emission tomography scans per- formed with a dopamine receptor radio-ligand [54].…”
Section: Pcm1 (Cg25454546) Aspscr1 (Cg23632389) Apc (Cg22035501) Larp...mentioning
confidence: 99%